Firms' excess savings and the Dutch current-account surplus: a stock-flow consistent approach - Huub Meijers; Joan Muysken; Olaf Sleijpen (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2016)
Retained profits of firms exceed investment in the Netherlands. The resulting net savings are mainly invested in foreign assets, which is consistent with the surplus on the current account of the balance of payments. Both have increased to almost 10 per cent of GDP in recent years. We present a stock-flow consistent model to explain firms' excess savings, inspired by Hein (2012), in an open economy context. This enables us to model the preference of firms to invest in financial assets abroad and to analyse the observed close link between firms' excess savings and the current-account surplus. As a consequence, we also explain the close relationship between net household savings and government budget deficit. We present simulation results to illustrate the workings of our model.
Keywords: E44; E6; F45; G32; 330; stock-flow consistent modelling; retained profits; current-account surplus